2021
DOI: 10.1088/1755-1315/886/1/012059
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of cave-dwelling bats in Leang Londrong, Bantimurung-Bulusaraung National Park: An initial field note

Abstract: Leang Londrong is one the caves in Maros-Pangkep Karst Formation utilized for nature tourism and has become a habitat for bats. Little is known on the bats inhabited the cave. Therefore, this study is aimed to investigate the diversity, abundance, morphometric of cave-dwelling bats in Leang Londrong, Bantimurung-Bulusaraung National Park as well as their distribution of roosting sites and micro-climate conditions between May-June 2021. The bats were trapped and collected by using two-layered mist nets erected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In one report, the species found were Hipposideros diadema and Miniopterus schreibersii [9]; while another study published in 2021 reported H. diadema, Rhinolopus arcuatus, and Myotis sp. roosting in the cave [10]. All the species found were Microchiropteran, which are mostly categorized as insectivore bats.…”
Section: Introductionmentioning
confidence: 99%
“…In one report, the species found were Hipposideros diadema and Miniopterus schreibersii [9]; while another study published in 2021 reported H. diadema, Rhinolopus arcuatus, and Myotis sp. roosting in the cave [10]. All the species found were Microchiropteran, which are mostly categorized as insectivore bats.…”
Section: Introductionmentioning
confidence: 99%